OTOMATISASI PENGUKURAN PENGUAPAN DAN PENGKONDISIAN TINGGI PERMUKAAN AIR PADA PANCI PENGUAPAN BERBASIS INTERNET OF THINGS - fauzi hasbi (Universitas Lampung, 2026)
Manual evaporation measurements using a Class A evaporation pan are prone to human error, particularly parallax error. Furthermore, the water level in the pan must be maintained within a standard range to ensure representative measurements and prevent the risk of the water level becoming too low or overflowing. This study aims to design an Internet of Things (IoT)-based automated system to measure evaporation while conditioning the water level in the pan. The system integrates ultrasonic and tipping bucket sensors, with measurement data monitored in real-time via a website. Water conditioning is automated using pumps to add or decrease water from the pan to achieve the standard water level before the daily measurement period begins. Test results show that the water conditioning system operates in accordance with the specified schedule and logic. Furthermore, the designed system is capable of performing automatic daily evaporation measurements, with a Mean Error (ME) of +0.76 mm and a Mean Absolute Error (MAE) of 2.06 mm.